Quantifying the sensitivity of barley seed germination to oxygen, abscisic acid, and gibberellin using a population-based threshold model - Bradford, Kent J (Journal of experimental botany, 2008)
Barley (Hordeum vulgare L.) seeds (grains) exhibit dormancy at maturity that is largely due to the presence of the glumellae (hulls) that reduce the availability of oxygen (O2) to the embryo. In addition, abscisic acid (ABA) and gibberellins (GAS) interact with O2 to regulate barley seed dormancy. A population-based threshold model was applied to quantify the sensitivities of seeds and excised embryos to O2, ABA, and GA, and to their interactive effects. The median O2 requirement for germination of dormant intact barley seeds was 400-fold greater than for excised embryos, indicating that the tissues enclosing the embryo markedly limit O2 penetration. However, embryo O2 thresholds decreased by another order of magnitude following after-ripening. Thus, increases in both permeability of the hull to O2 and embryo sensitivity to O2 contribute to the improvement in germination capacity during after-ripening. Both ABA and GA had relatively small effects on the sensitivity of germination to O2, but ABA and GA thresholds varied over several orders of magnitude in response to O2 availability, with sensitivity to ABA increasing and sensitivity to GA decreasing with hypoxia. Simple additive models of O2-ABA and O2-GA interactions required consideration of these O2 effects on hormone sensitivity to account for actual germination patterns. These quantitative and interactive relationships among O2, ABA, and GA sensitivities provide insight into how dormancy and germination are regulated by a combination of physical (O2 diffusion through the hull) and physiological (ABA and GA sensitivities) factors